Research and Implication of Traffic Analyzing Technology in Mobile Packet Network Based on DPI Technology - Yanrong Zhang; Zhizhong Zhang; Mingzhi Jiang; Xiaoping Zheng (Dianxin kexue)
With the rapidly developing of mobile internet and the commercial use of 4G, monitoring the service traffic becomes more and more important to operators. Firstly, a scheme for synthesizing xDR based on transport stream was given, after decoding preprocessing for the data of mobile packet network. Then the service identification and statistics of mobile packet network were implemented by using the complementary advantages for DPI（deep packet inspection）and DFI（deep flow inspection）technology. According to the test of current network data, this scheme works well for xDR synthesizing and service identification, with high efficiency and accuracy. It is of great significance to optimization of mobile packet network in 4G era.